Pragmatic Uses of Gestures in Brazilian Portuguese in Contexts of Negation (Revista de Estudos da Linguagem, 2024)
Drawing on discussions about the pragmatic functions of gestures, this study demonstrates how recurrent gestures in Brazilian Portuguese convey performative and metapragmatic functions in various communicative contexts of negation. To illustrate these pragmatic uses, we selected six examples of recurrent gestures performing distinct pragmatic functions from Brazilian TV shows, TED Talks, and legislative sessions. The dataset, comprising 565 samples (N = 565), was analyzed using the Methods of Gesture Analysis (MGA) and the Linguistic Annotation System for Gestures (LASG), focusing on gesture forms, functions, and their semantic relation with speech. Statistically significant results (p < 0.001) indicate that recurrent gestures used in contexts of negation in Brazilian Portuguese operate at a pragmatic level, contributing to the utterance’s illocutionary force, and often at a metapragmatic level, where they mark stancetaking and signal the speaker’s attitude toward the interlocutor.